Physiological analysis of drought tolerance of cucumber (Cucumis sativus) genotypes - FARAG, MOHAMED IBRAHIM; BEHERA, TUSAR KANTI; MUNSHI, ANILABH DAS; BHARADWAJ, CHELLAPILLA; JAT, GOGRAJ SINGH; KHANNA, MANOJ; CHINNUSAMY, VISWANATHAN (The Indian Journal of Agricultural Sciences, 2019)
Drought is one of the major factors limiting the growth and productivity of cucumber (Cucumis sativus L.) that adversely affects the desirable physiological and biochemical parameters. Thus, a field experiment was conducted during 2013â€“14 with 25 diverse genotypes of cucumber under four levels of irrigations, viz. 100% (control), 75%, 50% and 25% of the recommended irrigation. The yield reduction was as high as 51.97% under 25% of recommended irrigation. The physiological parameters such as proline, reducing sugars and phenol content increased significantly (P=0.05) as the drought stress increased from 100% irrigation to 25% irrigation level. In contrast, the relative water content (RWC), chlorophyll stability, membrane stability index (MSI) and fruit yield decreased signiï¬cantly (P=0.05) with the increase in the intensity of drought stress in all genotypes. Among 25 genotypes DGC-1, DGC-19 and WBC- 13 recorded better RWC, MSI, and lower yield reduction, while DGC-8, GS-3 and Barsati were highly sensitive to drought under all deficit irrigation levels (75%, 50% and 25%). These contrasting genotypes identified will be useful for mapping quantitative trait loci (QTLs) or genes for drought tolerance, and the best performing genotypes will be useful directly or as donors for genetic improvement in yield stability and water use efficiency in cucumber.